APLIKASI METODE DOUBLE DIFFERENCE DALAM RELOKASI HIPOSENTER UNTUK MENGGAMBARKAN ZONA TRANSISI ANTARA BUSUR BANDA DAN BUSUR SUNDA - Iis Nur Jannah; Titi Anggono; Tony Yulianto (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
The region along of zone transition between Banda arc and Sunda arc is very vulnerable region of earthquake disaster because of this region is located at active subduction zone which caused by convergent boundaries of two tectonic plate, Eurasian plate and Indo-Australian plates. Precise catalogue data will be important as references to tectonic and earthquake study in this area. Because that reason, precise hypocenter information is very important. Earthquake relocation is used to calculate earthquake hypocenter to become precisely. The purpose of this study is to get precise hypocenter distribution of zone transition between Banda arc and Sunda arc.The double-difference (DD) method is a relative hypocenter method using residual time data of pairs of events to each seismographic station. In this research used by using P wave travel time from the International Seismological Center (ISC). Earthquake that relocated are earthquake which recorded from 2014 until 2011. The results show relocated hypocenters move toward a certain structure and from a clear pattern of seismicity. A clear seismicity pattern is located in northern 119° which active subduction zone of two tectonic plate. The double-difference (DD) method can provide a significant improvement in the hypocenter location. This is indicated by residual time that decline.Keyword: relocation hypocenter, double-difference method, zone transition between Banda arc and Sunda arc.